Sistem Informasi Anggota Pramuka Berbasis Android (Kasus Kwartir Cabang Kota Tasikmalaya) - Fauzi, Rifki Amdan; Handayani, Rissa Nurfitriana; Yaqin, R. Ahmad Ainul; Rethanindita, Agung Widyangga; Taufiq, Irvan Hasbi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
Member scout identification, is an important identity for every Scout member. Nowadays, method of collecting data of member is conducted manually, and printed without saving the data of member owner, there is no system yet which could save the data of member card’s owner and update or remove the data if the member card was expired. And also the distance factor between Gugus Depan (School) and Kwartir Cabang, the place to register the prospective member, far enough, makes many potention data of scout members who are in the outlying place are not encoded. The aim of the research is to design and build a information system of the Scout Member Android Based in Kwartir Cabang Tasikmalaya City, o that it can solve the problem of saving and upgrading the potential data that can give the information fast and correctly. The collecting method uses observation and interview, while developing system uses waterfall model, which consists of stages analyst design, coding, and testing, also the helping tool to conduct the system program uses flowmap. While the implementation uses Android Studio and MySQL Database software. The result of this research is the Information of Scout Member’s System that makes the information process of scout member easier for the Scout members in Kwartir Cabang Tasikmalaya city.